Factors affecting phoneme discrimination in children with sequential bilateral cochlear implants. (1st April 2022) - Degirmenci Uzun, Erva; Batuk, Merve Ozbal; Sennaroglu, Gonca; Sennaroglu, Levent
Abstract: Objectives: To investigate the effects of a number of variables on phoneme discrimination (PD) performance in children with sequential bilateral cochlear implants (SeqBiCIs) and compare PD performance between the 2 implantation sides and between children with bilateral cochlear implants (BiCIs) and their age-matched peers with normal hearing (NH). Design: All participants completed the Auditory Speech Sound Evaluation Phoneme Discrimination Test. Study sample: The sample included 23 children with SeqBiCIs as the study group and 23 with NH as the control group. Results: A significant difference was found between the scores of the two groups under the CI1 and CI2 conditions ( p  = 0.001), CI1 and BiCI conditions ( p  = 0.002), and CI2 and BiCI conditions ( p  = 0.001). PD scores with CI1 significantly depend on age at CI1 and duration of bilateral use. PD scores with CI1 were significant predictors of PD performance with CI2 . Duration of BiCI use was a significant predictor of PD scores with BiCI. Conclusions: The age at CI1 and the duration of bilateral cochlear implant use were found to improve phoneme discrimination performance in children with a sequential bilateral cochlear implant. According to the success of the CI1, it is possible to predict the success of CI2 use.